Cybervictims and Cyberbystanders in an Ethnocultural-religious Context: Differences between Sectors in Israel - Lapidot-Leffler, Noam (International Dialogues on Education Journal, 2017)
The phenomenon of online bullying, which causes the victims a great deal of suffering, does not take place in a void, but rather it is related to the culture in which the bully and the victim were educated and to the context that gave rise to the bullying event. The current study constitutes an initial exploratory research that examined ethnocultural-religious aspects of online bullying in Israeli society. In particular, the researchers examined the influence of two variables on the rate of online bullying: participants’ ethnocultural-religious descent (Jewish, Muslim, and Christian citizens of Israeli) and the degree to which they believed in collectivist versus individualist principles. A total of 301 adolescents between the ages of 12 and 18 completed the following: an online questionnaire about cyberbullying, a questionnaire on individualism versus collectivism, and a questionnaire regarding demographic details. Findings indicated that the more participants’ cultural attitudes favored individualism, the less likely they were to be either witnesses to or victims of online bullying. These interesting findings will serve as a point of departure for discussing the online bullying phenomenon in the cultural and religious contexts of a multicultural society.